Designing of Loss Optimum Regulator for Control of D.C. Electric Drive with Varying Inertia Moment in CoDeSys Programming System - S. O. Novikov; A. V. Paschenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
CoDeSys programming system is considered as the most complete version of software for programmed logical controllers (PLC) that meets requirements of IEC 61131-3-standard. The given software is the most suitable for simulation and development of control system algorithms and execution of semi-full-scale tests without involvement of an actual object. Programming medium operated at a personal computer in Windows medium. As CoDeSys provides a machine code it is rather easy to support its programming and its minimum support presupposes selection of IN/OUT and program debugging functions.The investigations have been directed on optimization of an electric drive operation with varying inertia moment. The whole software developed for the solution of the considered problem, has been written and realized in the CoDeSys programming system. «Modified principle of maximum» of V. I. Panasiuk is applied as a body of mathematics that allows to obtain positive results of the investigations.